Subaru/FOCAS IFU revealed the metallicity gradient of a local extremely metal-poor galaxy. (2nd November 2021) - Kashiwagi, Yuri; Inoue, Akio K; Isobe, Yuki; Nakajima, Kimihiko; Ouchi, Masami; Ozaki, Shinobu; Fujimoto, Seiji; Ono, Yoshiaki; Kojima, Takashi
Abstract: We present the first measurement of the metallicity gradient in extremely metal-poor galaxies (EMPGs). With Subaru/Faint Object Camera And Spectrograph (FOCAS) Integral Field Unit (IFU), we have observed a nearby, low-mass EMPG, HSC J1631+4426, whose oxygen abundance and stellar mass are known to be 12 + log (O/H) = 6.9 and log10 ( M * / M ⊙ ) = 5.8, respectively. The measured metallicity gradient is −0.36 ± 0.04 dex kpc −1 corresponding to −0.049 ± 0.006 dex\:R_e^-1 for the continuum effective radius of R e = 0.14 kpc. Our observation has successfully demonstrated that three-dimensional spectroscopy with 8 m-class telescopes is powerful enough to reveal the metallicity distribution in local EMPGs, providing precious information on the baryon cycle in local analogs of primordial galaxies in the early Universe.